Coated Cutting Tools

By depositing (Ti,Al) N layers with specific Ti:Al ratio and columnar particle structure on metal cutting tools, the problem of excellent wing wear of existing tools during steel cutting is solved, achieving longer tool life and better cutting performance.

JP7656614B2Active Publication Date: 2025-04-03WALTER AG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022537097
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-17
Publication Date
2025-04-03
Estimated Expiration
2040-12-17

Smart Images

  • Figure 0007656614000006
    Figure 0007656614000006
  • Figure 0007656614000007
    Figure 0007656614000007
  • Figure 0007656614000008
    Figure 0007656614000008
Patent Text Reader

Abstract

The present invention is based on the overall composition (Ti x Al 1-x )N, 0.34≦x≦0.65, wherein the (Ti,Al)N layer contains columnar (Ti,Al)N grains having an average grain size of 10 to 100 nm, the (Ti,Al)N layer contains lattice planes of a cubic crystal structure, and the (Ti,Al)N layer has a lattice plane of 3.2 to 4.0 nm in an electron diffraction analysis. -1 The peak (P) in the averaged radial intensity distribution profile has its maximum value within the scattering vector range of 0.8-2.0 nm. -1 The present invention relates to a coated cutting tool exhibiting a pattern in which there is a diffraction signal where
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated cutting tool having a coating comprising a (Ti,Al)N layer. [Background technology]

[0002] There is a continuing desire to improve cutting tools for metalworking to make them last longer and to withstand higher cutting speeds and / or other increasingly demanding cutting operations.

[0003] Generally, cutting tools for metalworking include a substrate of a hard material, such as cemented carbide, cubic boron nitride, or cermet, and a thin wear-resistant coating deposited on the surface of the substrate.

[0004] The performance of a coating depends on a complex interaction of different factors: both the physical and mechanical properties of the coating itself and the type of metalworking operation.

[0005] For the deposition of wear-resistant coatings, chemical vapor deposition (CVD) or physical vapor deposition (PVD) are commonly used. Both methods are limited in the coating properties they can provide. When coatings of the same chemical composition are deposited by either method, their properties vary, for example with respect to internal residual stress, density, and crystallinity.

[0006] The origin of the metallic elements in the coatings deposited by PVD is the so-called "target" in the PVD reactor. There are various PVD methods, broadly classified as cathodic arc evaporation and magnetron sputtering. Within the general term "magnetron sputtering", there are further methods that are very different from each other, such as dual magnetron sputtering and high power impulse magnetron sputtering (HIPIMS). Coatings provided using different methods differ in various aspects. Also, different combinations of process parameters used within the same type of PVD method will lead to differences between the deposited coatings, such as different physical properties, different mechanical properties, different crystal structures, different behavior when used in metal cutting processes, etc.

[0007] Titanium aluminum nitride (Ti,Al)N coatings deposited by physical vapor deposition (PVD) are well known. One type of (Ti,Al)N coating is a monolayer, where the (Ti,Al)N composition is essentially the same throughout the layer. Monolayer coatings are provided when one or more targets used in the deposition process have the same Ti:Al ratio. Another type of (Ti,Al)N coating is a multilayer, where there are (Ti,Al)N sublayers of different composition in the layer. Such a multilayer can be provided when at least two of the targets used in the deposition process have different Ti:Al ratios, so that sublayers of different composition are deposited alternately as the substrate rotates in the chamber. A special type of multilayer is the nanomultilayer, where the thickness of the individual layers may be as thin as only a few nanometers.

[0008] US 2018 / 0223436 A1 discloses a coated cutting tool having a cemented carbide substrate and a (Ti,Al)N coating. The coating includes a single or multi-layer wear-resistant protective layer, for example of (Ti,Al)N, deposited by a HIPIMS method.

[0009] US Patent Application Publication No. 2018 / 0030590(A1) describes a Ti alloy made by HIPIMS that has a long service life. 0.40 Al 0.60 Disclose the N layer. Summary of the Invention

[0010] It is an object of the present invention to provide a coated cutting tool which has improved flank wear in metal cutting, particularly in cutting steels, which reduces flank wear leading to improved tool life over prior art cutting tools.

[0011] The present invention Overall composition (Ti x Al 1-x )N, 0.34≦x≦0.65, wherein the (Ti,Al)N layer contains columnar (Ti,Al)N grains having an average grain size of 10-100 nm, and the (Ti,Al)N layer has an average grain size of 3.2-4.0 nm in electron diffraction analysis. -1 is shown as a peak (P) in the averaged radial intensity distribution profile having its maximum value within the range of the scattering vector of -1 Provided herein is a coated cutting tool exhibiting a pattern in which a diffraction signal is present, where

[0012] The averaged radial intensity profile is obtained from the electron diffraction pattern by taking the average of all the intensities of the diffraction pattern that have the same distance (radius) to the center of the diffraction pattern. The averaged intensity is then plotted as a function of radius.

[0013] The (Ti,Al)N layer suitably has an overall composition of (Ti x Al 1-x ) N, 0.35≦x≦0.55, preferably 0.36≦x≦0.45.

[0014] The (Ti,Al)N layer preferably contains columnar grains with an average width of 20 to 70 nm.

[0015] The peak (P) in the averaged radial intensity distribution profile is preferably between 3.4 and 3.8 nm. -1 , has its maximum value within the range of the scattering vector of

[0016] The full width at half maximum (FWHM) of the peak (P) is preferably 1.0 to 1.8 nm. -1 , preferably 1.2 to 1.6 nm -1 It is.

[0017] In one embodiment, the (Ti,Al)N layer is a (Ti,Al)N nanomultilayer consisting of 2-4, preferably 2, different (Ti,Al)N sublayers with different Ti:Al ratios. If the sublayers are very thin, there may not be a sharp boundary between two adjacent sublayers with different Ti:Al ratios. Instead, there may be a periodic gradual change in Ti:Al ratio throughout the thickness of the (Ti,Al)N nanomultilayer. For this reason, the Ti:Al ratio of a sublayer is considered herein to be the Ti:Al ratio present in the middle of the sublayer.

[0018] The sub-layer having the lowest Ti:Al ratio suitably has a Ti:Al ratio of from 0.10:0.90 to 0.50:0.50, preferably from 0.25:0.75 to 0.40:0.60.

[0019] The sub-layer having the highest Ti:Al ratio suitably has a Ti:Al ratio of from 0.30:0.70 to 0.70:0.30, preferably from 0.35:0.65 to 0.50:0.50.

[0020] The average thickness of the different types of (Ti,Al)N sub-layers is suitably 1-20 nm, preferably 1.5-10 nm, most preferably 1.5-5 nm.

[0021] The thickness of the (Ti,Al)N layer is suitably 0.4 to 20 μm, preferably 1 to 10 μm, most preferably 2 to 6 μm.

[0022] In this specification, the "grain size" of the (Ti,Al)N grains refers to the average grain width of the columnar (Ti,Al)N grains in the (Ti,Al)N layer. The grain width is measured in the center of the layer in a direction parallel to the coating surface. In one embodiment, the average grain size of the (Ti,Al)N grains is 10-80 nm, preferably 30-60 nm.

[0023] In one embodiment, the (Ti,Al)N layer has a thermal conductivity of 2.5-4.0 W / mK, preferably 3.0-3.6 W / mK. Low thermal conductivity is beneficial in keeping the heat load from the cutting process on the tool substrate as low as possible.

[0024] In one embodiment, the (Ti,Al)N layer has a Vickers hardness of 2600-3700 HV0.0015.

[0025] In one embodiment, the (Ti,Al)N layer has a reduced Young's modulus of 350-470 GPa.

[0026] The total thickness of the coating is suitably from 1 to 25 μm, preferably from 2 to 15 μm, most preferably from 3 to 10 μm.

[0027] The position of the maximum value of the peak (P) in the averaged radial intensity distribution profile in the electron diffraction analysis can be attributed to the diffraction signal of the lattice d-spacing present in the crystalline phase. Therefore, the maximum value of 3.2 to 4.0 nm -1 The position of the maximum of the peak (P) within the scattering vector range of 2.5-3.1 Å correlates to a d-spacing of 3.4-3.8 nm. -1 The location of the maximum of peak (P) within the scattering vector range will correlate to a d-spacing of 2.6-2.9 Å. Since there are no possible d-spacings in a cubic crystal structure greater than about 2.34 Å, the diffraction signal exhibiting peak (P) is believed in one embodiment to be from lattice planes of a hexagonal crystal structure, preferably (100) lattice planes.

[0028] The broadness of the peak (P) means that the size of the crystalline phase domains or crystallites is very small.

[0029] In one embodiment, a grain boundary phase is present between the (Ti,Al)N grains in the (Ti,Al)N layer. The grain boundary phase can be seen in TEM analysis as a very thin contrasting phase located between the individual (Ti,Al)N grains. The grain boundary phase suitably comprises a hexagonal crystal structure. The grain boundary phase suitably has an average thickness of 1 to 5 nm, preferably 1 to 3 nm.

[0030] In one embodiment, the (Ti,Al)N layer exhibits a pattern in electron diffraction analysis that includes diffraction signals from lattice planes of a cubic crystal structure.

[0031] In one embodiment, the diffraction signals from the lattice planes of the cubic crystal structure are ≦0.5 nm -1 , appropriately 0.10~0.4nm -1 , preferably 0.12 to 0.30 nm -1 The lattice planes of the cubic crystal structure exhibiting the diffraction signal are at least one of (111), (200), (220) and (222), suitably at least (111) and (200), preferably at least (111), (200) and (220), most preferably (111), (200), (220) and (222).

[0032] In one embodiment, the (Ti,Al)N layer has cubic (111) lattice planes with a preferred orientation within 40° + / - 15° from the normal to the coating surface, preferably within 40° + / - 10° from the normal to the coating surface. As used herein, the "preferred orientation" of the (hkl) lattice planes refers to the position of all (hkl) lattice planes where a certain tilt of the (hkl) lattice planes occurs most frequently. The preferred orientation of the lattice planes can be determined by XRD texture analysis, in particular from pole figures.

[0033] The substrate of the coated cutting tool may be of any type common in the field of cutting tools for metalworking, suitably selected from cemented carbide, cermet, cBN, ceramics, PCD and HSS.

[0034] In one preferred embodiment, the substrate is a cemented carbide.

[0035] The coated cutting tool can be a coated cutting insert, such as a coated cutting insert for turning or a coated cutting insert for milling or a coated cutting insert for drilling or a coated cutting insert for thread cutting or a coated cutting insert for parting and grooving, and the coated cutting tool can be a coated solid tool, such as a solid drill, end mill, tap, etc.

[0036] The (Ti,Al)N layer is preferably deposited by high power impulse magnetron sputtering (HIPIMS).

[0037] In one embodiment, the coating comprises a layer of metal nitride directly beneath the (Ti,Al)N layer. The metal nitride is suitably a nitride of one or more metals belonging to groups 4 to 6 of the IUPAC Periodic Table of the Elements, optionally with Al and / or Si. Examples of such metal nitrides include TiN and (Ti,Al)N. The thickness of the metal nitride layer is suitably 0.5-5 μm, preferably 1-3 μm. The metal nitride layer is preferably deposited by HIPIMS.

[0038] In one embodiment, the layer of metal nitride immediately below the (Ti,Al)N layer is (Ti y Al 1-y )N single layer, 0.30≦y≦0.90, preferably 0.33≦y≦0.70.

[0039] In a preferred embodiment, the coated cutting tool has an overall composition (Ti x Al 1-x )N, 0.34≦x≦0.65, the (Ti,Al)N layer containing columnar (Ti,Al)N grains having an average grain size of 10 to 100 nm, the (Ti,Al)N layer having an average grain size of 3.2 to 4.0 nm by electron diffraction analysis. -1is shown as a peak (P) in the averaged radial intensity distribution profile having its maximum value within the range of the scattering vector of -1 The (Ti,Al)N layer is a (Ti,Al)N nanomultilayer consisting of 2 to 4 different (Ti,Al)N sublayers with different Ti:Al ratios, in which the sublayer with the lowest Ti:Al ratio has a Ti:Al ratio of 0.25:0.75 to 0.40:0.60, and the sublayer with the highest Ti:Al ratio has a Ti:Al ratio of 0.35:0.65 to 0.50:0.50, and the average thickness of the different types of (Ti,Al)N sublayers is 1.5 nm to 5 nm. [Brief description of the drawings]

[0040] [Figure 1] FIG. 2 is a schematic diagram of an embodiment in which the cutting tool is a milling insert. [Diagram 2] FIG. 2 shows an electron diffraction image of a (Ti,Al)N layer according to the present invention. [Diagram 3] FIG. 1 shows an electron diffraction image of a (Ti,Al)N layer according to the prior art. [Figure 4] FIG. 1 shows a fitted average radial intensity distribution curve constructed for the electron diffraction pattern of a (Ti,Al)N layer according to the present invention. [Diagram 5] FIG. 1 shows a fitted average radial intensity distribution curve constructed for the electron diffraction pattern of a (Ti,Al)N layer according to the prior art (Reference 2). [Figure 6] 1 is a schematic diagram of a crystal grain structure in which a grain boundary phase exists at some of the grain boundaries. [Figure 7] TEM image of a (Ti,Al)N layer according to the invention, where several grains are underlined. [Figure 8] FIG. 8 shows the intensity profile for the line drawn in FIG. [Figure 9] FIG. 1 shows a TEM image of a (Ti,Al)N layer according to the invention showing the (Ti,Al)N grains. [Figure 10]FIG. 10 shows an enlarged portion of FIG. 9 showing (Ti,Al)N grains surrounded by grain boundary phase shown in black. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] The embodiment of the present invention is further explained in the attached drawings, Fig. 1, Fig. 6, Fig. 7 and Fig. 9. Fig. 1 is a schematic diagram of an embodiment of a cutting tool (1) having a rake face (2), a flank face (3) and a cutting edge (4). The cutting tool (1) is a milling insert in this embodiment. Fig. 6 shows a schematic diagram of the grain structure of a (Ti,Al)N layer according to the invention having (Ti,Al)N grains (5) with a grain boundary phase (6) present at some of the grain boundaries between adjacent (Ti,Al)N grains (5). Fig. 7 shows a TEM image of a (Ti,Al)N layer according to the invention, where lines have been drawn over several grains. The intensity profile for the drawn lines is shown in Fig. 8. The grain boundaries contain a dark phase on the image, so that there is a large drop in intensity beyond these grain boundaries. This allows the thickness of the grain boundary phase to be estimated. Fig. 9 shows the same TEM image as Fig. 7, but with increased contrast so that the grain boundary phase is more clearly visible. In the figure, a mark has been drawn around one (Ti,Al)N grain. Figure 10 is an enlarged view of the marked area around one (Ti,Al)N grain in Figure 9. The black grain boundary phase is clearly visible around the (Ti,Al)N grain.

[0042] method XRD Texture Analysis (Pole Figures) For the analysis of the crystallographic texture, a Seifert / GE diffractometer (PTS3003) was used to determine the preferred orientation of the lattice planes in the (Ti,Al)N layers. The analysis was performed using a CuK α A line was applied (high voltage 40 kV, current 40 mA). The incident beam was defined by a 2 mm pinhole. An energy dispersive detector (Meteor 0D) was used in the path of the diffracted beam. Pole figures were obtained from measurements made with the α axis tilted in 5° increments from 0 to 80° and the β axis tilted in 5° increments from 0 to 360°.

[0043] TEM analysis Transmission electron microscopy data (selected area diffraction patterns and dark field images) were obtained using a JEOL (Jeol ARM) transmission electron microscope. A high voltage of 300 kV was used for the analysis.

[0044] Where electron diffraction experiments are referred to herein, these are TEM measurements performed with parallel illumination. Regions of interest were selected with a selected-field aperture.

[0045] For the preparation of the TEM samples, a FIB (focused ion beam) lift-out was used. For the final polishing, the Ga ion beam was adjusted to a current of 200 pA at 5 kV.

[0046] A cross section of the coating was analyzed perpendicular to the surface of the coating.

[0047] The small intensities in the diffraction pattern can be analyzed by using intensity profile analysis. Gaussian fitting of the entire curve was performed to extract the individual diffraction intensity peaks from the averaged radial intensity distribution profile. The software used was HighScore version 4.8 from Malvern Panalytical.

[0048] To analyze the elemental distribution throughout the layer, for example to obtain the Ti:Al ratio at a particular location in the layer, it is preferred to use a TEM EDS linescan using STEM mode, 300 kV.

[0049] Analysis of the thickness of the grain boundary phase was performed by image analysis by determining the change in brightness of the TEM image along a crossed line. The grain boundary phase is dark on the image so that the thickness can be determined. A sufficient length and / or number of crossed lines are drawn to provide a reliable average value of the grain boundary phase thickness. Suitably, at least 20 grain boundaries are crossed and an average value is calculated.

[0050] Vickers hardness The Vickers hardness was measured by nanoindentation (load-depth graph) using a Picodentor HM500 from Helmut Fischer GmbH (Sindelfingen, Germany). For the measurements and calculations, the Oliver and Pharr evaluation algorithm was applied, where a diamond specimen from Vickers was pressed into the layer and the force-path curve was recorded during the measurement. The maximum load used was 15 mN (HV 0.0015), the load increase and load decrease times were 20 s each, and the hold time (creep time) was 10 s. The hardness was calculated from this curve.

[0051] Decreased Young's modulus The reduced Young's modulus (reduced elastic modulus) was determined by nanoindentation (load-depth graph) as described for determining Vickers hardness.

[0052] Fracture toughness The following steps were followed: The coating is deposited on a polished cemented carbide substrate (Co 8 wt%) with a flat square shape and side length of 15 mm. The surface roughness is further reduced using soft opus polishing. The sample is then ultrasonically cleaned in ethanol and transferred to the FIB-SEM instrument. A protective platinum layer is deposited using precursor gases and Ga ions from the FIB. The holed disk is milled down to below the substrate with the FIB. The result is free-standing micropillars (~5 μm) on the substrate.

[0053] The sample is then transferred to an indentation system. The tip of the indenter is aligned over the pillar. Load-depth curves are acquired and crack initiation is confirmed. Using mathematical models, fracture toughness values ​​are calculated. See also M. Sebastiani, Current Opinion in Solid State and Materials Science, vol. 19 (2015), no. 6, pp. 324-333.

[0054] (Ti,Al)N particle size The method used was the line segment intersection method. The surface of the sample was polished with an OPS suspension until a flat surface was obtained. Afterwards, a medium magnification (approximately 10,000x) was used.

[0055] An intensity profile of 1-2 μm length was taken in at least one of the images, and grain boundaries were seen as a significant decrease in intensity. The average distance between two adjacent grain boundaries, i.e. the diameter of the columnar grains, was taken as the average grain size. The measurements were taken at the center of the layer thickness, approximately 1 mm away from the cutting edge on the rake side of the ground insert.

[0056] Thermal Conductivity A time domain thermoreflectance (TDTR) method was used with the following characteristics: 1. A laser pulse (pump) is used to locally heat the sample. 2. Thermal energy is transferred from the sample surface to the substrate due to thermal conductivity and heat capacity. The surface temperature decreases over time. 3. The fraction of the laser that is reflected depends on the surface temperature. A second laser pulse (the probe pulse) is used to measure the temperature drop at the surface. 4. Using mathematical models, it is also possible to calculate the thermal conductivity from the heat capacity values ​​of the samples. (See DG Cahill, Rev. Sci. Instr. 75, 5119 (2004)).

[0057] Thickness The thickness of the coating layer was determined by carrot grinding, whereby a dome-shaped recess was ground using a steel ball with a diameter of 30 mm, and the diameter of the ring was measured and the layer thickness was calculated from it. The layer thickness measurements on the rake face (RF) of the cutting tool were performed at a distance of 2000 μm from the corner, and on the flank face (FF) at the center of the flank face. EXAMPLES

[0058] Example 1 (Invention) Ti was deposited on a WC-Co based cutting insert substrate using HIPIMS mode on a 6-flange INGENIA S3p (Oerlikon Balzers) tool.40 Al 60 A layer of N was deposited.

[0059] The substrate had a composition of 12 wt% Co, 1.6 wt% (Ta,Nb)C, and the remainder WC, with a WC grain size, dWC, of ​​about 0.8 μm. The cutting insert had the geometry ADMT160608R-F56.

[0060] 160mm diameter circular Ti 40 Al 60 Six targets were used. HIPIMS Ti with a thickness of about 2 μm 40 Al 60 The N monolayer was deposited using the following deposition parameters: Total pressure: 0.59Pa Ar pressure: 0.43 Pa (the rest is filled with N2 to the full pressure) Bias DC voltage: -40V Temperature: 430℃ Power: 60kW Average power per target: 9.04kW Pulse lighting time: 7.56μs Frequency: 20Hz #Repeat:1

[0061] Next, the average composition Ti was measured by HIPIMS. 36 Al 64 The target was a circular target with a diameter of 160 mm, and a layer of wear-resistant (Ti,Al)N with a thickness of about 1.8 μm was deposited. 33 Al 67 3 targets, Ti 40 Al 60 A total of six N targets were used, three of which were N. The following deposition parameters were used: Total pressure: 0.64Pa (7 minutes) 0.61Pa (52 minutes) Ar pressure: 0.43 Pa (the rest is filled with N2 to the full pressure) Bias DC voltage: -40V Temperature: 430℃ Power: 60kW Illumination time: Ti33Al67: 2.00ms, Ti40Al60: 2.53ms Average power per target: Ti33Al67: 7.2kW, Ti40Al60: 9.0kW

[0062] Example 2 (Reference 1) A comparative prior art sample, “Reference 1”, was prepared by depositing Ti on a WC-Co based cutting insert substrate using HIPIMS mode on a 6-flange INGENIA S3p (Oerlikon Balzers) instrument. 40 Al 60 A layer of N was deposited.

[0063] The substrate had a composition of 12 wt% Co, 1.6 wt% (Ta,Nb)C, and the remainder WC, with a WC grain size, dWC, of ​​about 0.8 μm. The cutting insert had the geometry ADMT160608R-F56.

[0064] 160mm diameter circular Ti 40 Al 60 Six targets were used. 40 Al 60 Using the same deposition parameters as for the N monolayer, a ~4 μm thick HIPIMS Ti 40 Al 60 A monolayer of N was deposited.

[0065] Example 3 (Reference 2) A comparative sample according to the prior art, "Reference 2", was prepared using the HIPIMS mode on an HTC1000 Hauzer instrument. 33 Al 67 N / Ti 50 Al 50 Coatings containing multiple layers of N were deposited on WC-Co based cutting insert substrates.

[0066] The substrate had a composition of 12 wt% Co, 1.6 wt% (Ta,Nb)C, and the remainder WC, with a WC grain size, dWC, of ​​about 0.8 μm. The cutting insert had the geometry ADMT160608R-F56.

[0067] The coating deposited was essentially the same as that disclosed in US Patent Application Publication No. 2018 / 0223436 A1, Example 2. The coating was deposited as follows.

[0068] First, the bonding layer was formed by deposition in two steps: Ti 50 Al 50 A first portion of the bonding layer consisting of an approximately 50 nm thick layer of N was deposited in step 1 by arc evaporation.

[0069] Step 1: Target TiAl (50:50), diameter 63 mm, reactor position 2 Deposition parameters Time: 3 minutes Vaporizer current: 75A Flow rate adjustment: 3500sccm N2 Bias DC voltage: 60V

[0070] Next, in step 2, Ti 33 Al 67 N and Ti 50 Al 50 A second portion of the bonding layer was deposited consisting of an approximately 0.2 μm thick (Ti,Al)N multilayer of alternating sublayers of N for a total of about six sublayers.

[0071] Step 2: Target 1: TiAl (33:67), diameter 63 mm, reactor position 5, Target 2: TiAl (50:50), diameter 63 mm, reactor position 2 (opposite side) Deposition parameters Time: 3 minutes Vaporizer current: 75A Flow rate adjustment: 3500sccm N2 Bias DC voltage: 40V

[0072] A wear-resistant (Ti,Al)N multilayer was then deposited by HIPIMS using the following deposition parameters: Target size Hauzer: Rectangle 17cm x 83cm x 1cm Average power: 36kW (18kW per target) Bias DC voltage: 100V Peak current: Target 1: 170A, Target 2: 170A Reaction gas: 180sccm N2, pressure adjusted, 0.53Pa (500sccm Ar) Pulse file: 60 Temperature: 550℃

[0073] The deposited wear-resistant (Ti,Al)N multilayer was 2.7 μm thick and consisted of approximately 760 alternating individual TiAlN sublayers.

[0074] Example 4 (Analysis) TEM analysis with electron diffraction analysis Images of the (Ti,Al)N layers of the samples of Examples 1 to 3 were made by transmission electron microscopy (TEM). Figures 7 and 9 respectively show images of samples according to the invention, in which the grain boundary phase between the (Ti,Al)N grains can be seen around the (Ti,Al)N grains. However, such grain boundary phase was not seen in the images of the comparative samples "Reference 1" and "Reference 2". Image analysis of the TEM images of the samples according to the invention shows that the grain boundary phase is about 2 to 3 nm thick.

[0075] Furthermore, electron diffraction analysis was carried out in TEM on a sample according to the invention, prepared according to the procedure of Example 1, and on a comparative sample "Reference 2", prepared according to the procedure of Example 3.

[0076] 2 and 3 show the electron diffraction patterns of the samples, respectively.

[0077] As is clear from FIG. 2, the sample according to the present invention has a particle size of about 4.1 nm as seen by the naked eye. -1 For the lower scattering vectors, very clear diffraction spots or any ring-like patterns are not visible. However, FIG. 4 shows the average radial intensity distribution curve generated for the electron diffractogram of a sample according to the invention. This curve shows the presence of a broad peak, which can be seen as a clear shoulder in the total intensity curve, and after curve fitting (Gaussian fit, noise removal), the broad peak is located at about 3.6 nm.-1 The diffraction pattern has its maximum at a scattering vector of 10 nm (corresponding to a d-spacing of about 2.8 Å). -1 The figure shows six additional signals with scattering vectors up to 1000 nm. See Table 1 for the d-spacings and FWHM values ​​of the corresponding peaks. In addition, the d-spacings near the cubic and hexagonal crystal structures from the standard TiAlN (TiN+AlN solid solution) diffraction pattern are included in the table. TIFF0007656614000001.tif87170

[0078] The full width at half maximum (FWHM) of the peak is 1.44 nm -1 and is a measure of the broadness of the peak.

[0079] When the average radial intensity distribution curve is constructed for the electron diffraction pattern of the comparative sample "Reference 2", there is no broad peak as seen in the samples according to the invention (see FIG. 5).

[0080] Without wishing to be bound by theory, it is believed that the origin of the broad peak at low scattering vectors in the samples according to the invention is from a phase with a very small structure, as mentioned above. From the TEM images, there is evidence of a grain boundary phase in the (Ti,Al)N layer according to the invention, but not in the (Ti,Al)N layers of either Reference 1 or Reference 2. The thickness of the grain boundary phase in the (Ti,Al)N layer according to the invention is estimated to be about 3 nm. The broadness of the peak is believed to reflect the small structure of this grain boundary phase.

[0081] XRD analysis A polar plot search of the (111) lattice plane reflection was performed for the sample according to the invention and the comparative sample "Reference 2". The results showed that for the sample according to the invention, there is a preferred orientation of the (111) lattice plane at about 40 degrees from the normal to the coating surface. For the comparative sample, there are two preferred orientations of the (111) lattice plane, one at about 15 degrees from the normal to the coating surface and one at about 60 degrees from the normal to the coating surface.

[0082] particle size From the scanning electron microscope (SEM), the size of the (Ti,Al)N grains was determined by the line segment intersection method for both the sample according to the invention and the reference sample, and the results are shown in Table 2. TIFF0007656614000002.tif54170

[0083] Mechanical properties In addition, hardness measurements (load 15 mN) were performed on the flank of the coated tool, and the Vickers hardness, reduced Young's modulus (EIT), and fracture toughness (K Ic ) was measured. The results are shown in Table 3. To characterize the toughness (Young's modulus) of the coating, a Vickers indentation was performed with a load of 500 mN and a cross section was prepared. TIFF0007656614000003.tif63170

[0084] Thermal Conductivity Finally, the thermal conductivity was measured for the coating according to the invention. The specific heat capacity value was required and was 2.79 J / cm for the coating according to the invention. 3 Using a value of K, for reference 1 it is 2.81 J / cm 3 We used values ​​of K, see Table 4. TIFF0007656614000004.tif53170

[0085] Example 4 (Cutting test) Milling tests were carried out.

[0086] Work material: Steel 42CrMo4 (ISO-P) Tooth feed, fz [mm]: 0.2 Approach angle, κ [°]: 90 Cutting width, ae[mm]:98 Cutting depth, ap [mm]: 3 Cutting speed, vc [m / min]: 185 Rotation speed, s [U / min]: 470

[0087] The criterion for terminating the cutting test was tool flank wear of more than 0.1 μm. The results are shown in Table 5. TIFF0007656614000005.tif76170

[0088] It can be concluded that the cutting tool comprising the (Ti,Al)N layer according to the present invention has the best performance in terms of flank wear leading to a longer tool life.

Claims

1. Overall composition (Ti x A 1-x )N, 0.34≦x≦0.65, wherein the (Ti,Al)N layer comprises columnar (Ti,Al)N grains having an average grain size of 10-100 nm, the (Ti,Al)N layer comprises lattice planes of a cubic crystal structure, and the (Ti,Al)N layer exhibits a lattice plane distribution of 3.2-4.0 nm by electron diffraction analysis. -1 , and the full width at half maximum (FWHM) of the peak (P) is between 0.8 and 2.0 nm. -1 4. A coated cutting tool showing a pattern in which there is a diffraction signal where

2. The (Ti,Al)N layer has an overall composition (Ti x A 1-x 2. The coated cutting tool of claim 1 , wherein N, 0.35≦x≦0.

55.

3. The peak (P) in the averaged radial intensity distribution profile is between 3.4 and 3.8 nm. -1 3. The coated cutting tool according to claim 1, wherein the scattering vector of the cutting tool has a maximum value within a range of

4. Peak (P) full width at half maximum (FWHM) is 1.0 to 1.8 nm -1 The coated cutting tool according to claim 1 ,

5. 5. The coated cutting tool according to claim 1 , wherein the (Ti,Al)N-layer is a (Ti,Al)N nano-multilayer consisting of 2 to 4 different (Ti,Al)N sub-layers having different Ti:Al ratios from each other.

6. 6. The coated cutting tool of claim 5, wherein the sub-layer having the lowest Ti:Al ratio has a Ti:Al ratio of 0.10:0.90 to 0.50:0.50 and the sub-layer having the highest Ti:Al ratio has a Ti:Al ratio of 0.30:0.70 to 0.70:0.

30.

7. The coated cutting tool according to any one of claims 1 to 6, wherein the (Ti,Al)N layer has a thickness of 0.4 to 20 μm.

8. The coated cutting tool according to any one of claims 1 to 7, wherein the (Ti,Al)N layer has a thermal conductivity of 2.5 to 4.0 W / mK.

9. A coated cutting tool according to any one of claims 1 to 8, wherein the (Ti,Al)N layer has a Vickers hardness of 2600 to 3700 HV0.0015.

10. A coated cutting tool according to any one of claims 1 to 9, wherein the (Ti,Al)N has a reduced Young's modulus of 350 to 470 GPa.

11. A coated cutting tool according to any one of claims 1 to 10, wherein the coating has an overall thickness of 1 to 25 µm.

12. The coated cutting tool according to claim 1 , wherein a grain boundary phase is present between the (Ti,Al)N grains in the (Ti,Al)N layer.

13. The coated cutting tool of claim 12, wherein the grain boundary phase has an average thickness of 1 to 5 nm.

14. 14. The coated cutting tool according to any one of claims 1 to 13, wherein the diffraction signal exhibiting a peak (P) is attributable to a hexagonal crystal structure.

15. 15. The coated cutting tool of any one of claims 1 to 14, wherein the (Ti,Al)N layer exhibits in electron diffraction analysis a pattern including diffraction signals from lattice planes of a cubic crystal structure, the lattice planes of the cubic crystal structure being at least one of a (111), (200), (220) or (222) lattice plane.

16. 16. The coated cutting tool of claim 15, wherein cubic (111) lattice planes are present in the (Ti,Al)N layer, and the (111) lattice planes have a preferred orientation within 40 degrees + / - 15 degrees of a direction normal to the coating surface.

17. 17. The coated cutting tool of any one of claims 1 to 16, wherein the substrate is selected from cemented carbide, cermet, cBN, ceramics, PCD and HSS.

Citation Information

Patent Citations

  • Coated cutting tool for general turning of heat-resistant super-alloy

    JP2009090452A

  • Titanium aluminum nitride coating and method for producing the same

    JP2013506567A

  • Surface coated cutting tool excellent in abnormal damage resistance and abrasion resistance

    JP2016026893A

  • Surface coated cutting tool with hard-coated layer exhibiting superior chipping resistance

    JP2016168669A

  • Composite structured wear resistant coating

    US20040115484A1